2011
DOI: 10.1267/ahc.10029
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mTOR Inhibition-Involved Pathway in Ovarian Clear Cell Adenocarcinoma

Abstract: This study was designed to clarify the mechanism of the mammalian target of rapamycin (mTOR)-hypoxia inducible factor-1 (HIF-1) pathway using the cultured cell strain derived from human ovarian clear cell adenocarcinoma (CCA). Everolimus (a derivative of rapamycin)-treated cells and non-treated cells did not show any difference in mTOR expression. But, phosphorylated-mTOR (p-mTOR) expression significantly decreased in the treated cells, and mTOR-related factors such as phosphorylated-4E-BP1 (p-4E-BP1), HIF-1α,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…These results are consistent with previous studies demonstrating a decrease in the translation of HIF-1a following inhibition of the PI3K signaling cascade. 36,37 Our results are also consistent with previous reports of decreased HIF-1a levels in several cancer models following treatment with everolimus 38 or LY294002. 39 HIF-1 is known to regulate the expression of ChoKa 23 and several glycolytic enzymes, including LDHA.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous studies demonstrating a decrease in the translation of HIF-1a following inhibition of the PI3K signaling cascade. 36,37 Our results are also consistent with previous reports of decreased HIF-1a levels in several cancer models following treatment with everolimus 38 or LY294002. 39 HIF-1 is known to regulate the expression of ChoKa 23 and several glycolytic enzymes, including LDHA.…”
Section: Discussionsupporting
confidence: 92%
“…We previously analyzed the expression of cleaved caspase-3 among various apoptosisrelated factors, and our in vitro study showed no expression of cleaved caspase-3 in the untreated group. 23 Inhibition of mTOR is considered to have led to cell death and apoptosis. These results suggest that everolimus not only inhibits mTOR signaling but also promotes VHL expression and that everolimus exhibits antitumor activity through inhibition of HIF-1> expression.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that everolimus not only inhibits mTOR signaling but also promotes VHL expression and that everolimus exhibits antitumor activity through inhibition of HIF-1> expression. 23 Further analysis of VHL expression could lead to the identification of a new mediator in the intracellular signaling system. The efficacy of everolimus has primarily been studied in patients with renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experiments using animals sometimes show differences in the reaction between humans and animals. To solve these problems, immunodeficient nu/nu mice or scid/scid mice have been widely used as in vivo models with human characteristics because various human tissues, including oral mucosa, can be transplanted into these mice [8, 10, 22, 31]. In oral mucosa, transplanted grafts frequently show cystic formation [10].…”
Section: Introductionmentioning
confidence: 99%